2013
DOI: 10.1074/jbc.m113.470047
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-O-GlcNAcylation Is Anti-apoptotic and Maintains Constitutive NF-κB Activity in Pancreatic Cancer Cells

Abstract: Background: Cancer cells rely on energy metabolism that requires increased glucose uptake and constitutive NF-B activity for survival. Results: Pancreatic cancer cells display elevated O-GlcNAcylation, reduction of which inhibits cell survival and oncogenic NF-B signaling. Conclusion: Hyper-O-GlcNAcylation is anti-apoptotic and contributes to NF-B activation in pancreatic cancer. Significance: Targeting hyper-O-GlcNAcylation may serve as a novel therapeutic intervention in pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
226
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(247 citation statements)
references
References 47 publications
18
226
0
3
Order By: Relevance
“…Consequently, cancer cell metabolic changes, including increased glucose uptake due to the Warburg effect and increased glutamine uptake, likely cooperate to drive increased HBP flux. In support of this, we found that the end products of the HBP (including UDP-GlcNAc) are elevated in pancreatic cancer cells (15). Thus, it appears that increased HBP flux and elevated UDPGlcNAc are general features of cancer cells that contribute to hyper-O-GlcNAcylation.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…Consequently, cancer cell metabolic changes, including increased glucose uptake due to the Warburg effect and increased glutamine uptake, likely cooperate to drive increased HBP flux. In support of this, we found that the end products of the HBP (including UDP-GlcNAc) are elevated in pancreatic cancer cells (15). Thus, it appears that increased HBP flux and elevated UDPGlcNAc are general features of cancer cells that contribute to hyper-O-GlcNAcylation.…”
supporting
confidence: 67%
“…Indeed, we found that reducing hyper-O-GlcNAcylation in the pancreatic ductal adenocarcinoma cell lines MiaPaCa-2 and PANC-1 decreases the expression of the anti-apoptotic protein Bcl-x L and induces pro-apoptotic cleavage of caspase-9 and caspase-3. These results indicate that reducing pancreatic cancer cell hyper-O-GlcNAcylation triggers the intrinsic apoptotic pathway (15). Conversely, increasing O-GlcNAc in pancreatic cancer BxPC-3 cells protects against suspension-induced apoptosis (15).…”
Section: O-glcnac and Cancer Cell Survivalmentioning
confidence: 91%
See 1 more Smart Citation
“…As a nutrient sensor, O-GlcNAc relays the effects of excessive nutritional intake, an important cancer risk factor, onto protein activities and cellular functions (8). Indeed, major tumor suppressors and oncoproteins, such as p53, MYC, NF-κB, and β-catenin are direct targets of O-GlcNAc (12)(13)(14)(15)(16)(17). Chromatin dynamics is also modulated by O-GlcNAc.…”
mentioning
confidence: 99%
“…cancers (16,19,20), but neither has been examined previously in the context of HPV oncogene expression or cervical neoplasms. In this work, we asked whether O-GlcNAc might play a role in HPVinduced transformation and carcinogenesis.…”
mentioning
confidence: 99%